2021
DOI: 10.18203/2320-1770.ijrcog20212147
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum vitamin D levels with gestational diabetes mellitus

Abstract: Background: This study was done to evaluate the association of serum vitamin D level with GDM (n=30) and without GDM (n=30). The age and body mass index of the participants along with their gestational age, gravidity and parity were harmonized. The serum vitamin D levels and blood glucose were investigated. The results revealed that, normal pregnant women had significantly higher vitamin D level than their GDM counterparts.Methods: This case-control study was conducted on healthy pregnant women attending routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…In research conducted by Zhang et al (2008), Tacoma (2013), Liu et al (2011) and Mahmood (2021), similar results were also obtained that vitamin D (25(OH)D) deficiency was evident in women who developed GDM was compared in controls, which is consistent with most of the cross-sectional and case-control studies discussed in which GDM patients were more likely to be vitamin D deficient or have lower serum 25-hydroxyvitamin D. In Zhang et al's study, there was a 2.66 x risk of developing GDM in subjects with vitamin D deficiency. Based on research conducted by Zhang, et al in 2015 showed a consistent relationship between vitamin D deficiency and an increased risk of GDM.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In research conducted by Zhang et al (2008), Tacoma (2013), Liu et al (2011) and Mahmood (2021), similar results were also obtained that vitamin D (25(OH)D) deficiency was evident in women who developed GDM was compared in controls, which is consistent with most of the cross-sectional and case-control studies discussed in which GDM patients were more likely to be vitamin D deficient or have lower serum 25-hydroxyvitamin D. In Zhang et al's study, there was a 2.66 x risk of developing GDM in subjects with vitamin D deficiency. Based on research conducted by Zhang, et al in 2015 showed a consistent relationship between vitamin D deficiency and an increased risk of GDM.…”
Section: Discussionmentioning
confidence: 96%
“…Vitamin D also has important functions in pregnancy such as maintaining the balance of glucose metabolism, controlling inflammation and infection responses. Several studies have reported that vitamin D deficiency is also associated with an increased risk of preeclampsia, gestational diabetes mellitus, low birth weight, and premature birth (Mahmood et al, 2021).…”
Section: Introductionmentioning
confidence: 99%